Glycine receptor antibody mediated Progressive Encephalomyelitis with Rigidity and Myoclonus (PERM): a rare but treatable neurological syndrome. Issue 2 (5th April 2013) - Stern, W M; Howard, R; Chalmers, R M; Woodhall, M R; Waters, P; Vincent, A; Wickremaratchi, M M
Abstract : A 40-year-old man presented with respiratory compromise and was intubated. After tracheostomy, he was found to have ophthalmoplegia, severe limb rigidity, stimulus-sensitive myoclonus and autonomic dysfunction. For 1 week before admission, there had been a prodromal illness with low mood, hallucinations and limb myoclonus. Serum glycine receptor antibodies were strongly positive: we diagnosed progressive encephalomyelitis with rigidity and myoclonus. Despite a relapse, he has done well following immunotherapies. The clinical syndrome of encephalomyelitis with rigidity, described in 1976, often has a severe progressive course. A minority of patients have glutamic acid decarboxylase antibodies. The association with glycine receptor antibody was first reported in 2008, and we briefly review subsequent case reports to illustrate the range of clinical features. The antibody is likely to be disease mediating, although this remains unproven. The spectrum of diagnosable and treatable antibody mediated neurological syndromes is expanding. It is vital to recognise these conditions early to reduce morbidity and mortality.